Banksia species (Proteaceae) from severely phosphorus-impoverished soils exhibit extreme efficiency in the use and re-mobilization of phosphorus - DENTON, MATTHEW D; VENEKLAAS, ERIK J; FREIMOSER, FLORIAN M; LAMBERS, HANS (Plant, cell and environment, 2007)
Banksia species (Proteaceae) occur on some of the most phosphorus (P)-impoverished soils in the world. We hypothesized that Banksia spp. maximize P-use efficiency through high photosynthetic P-use efficiency, long leaf lifespan (P residence time), effective P re-mobilization from senescing leaves, and maximizing seed P concentration. Field and glasshouse experiments were conducted to quantify P-use efficiency in nine Banksia species. Leaf P concentrations for all species were extremely low (0.14-0.32 mg P g⁻¹ DM) compared with leaf P in other species reported and low relative to other plant nutrients in Banksia spp.; however, moderately high rates of photosynthesis (13.8-21.7 μmol CO₂ m⁻² s⁻¹), were measured. Some of the Banksia spp. had greater P proficiency (i.e. final P concentration in senesced leaves after re-mobilization; range: 27-196 μg P g⁻¹ DM) than values reported for any other species in the literature. Seeds exhibited significantly higher P concentrations (6.6-12.2 mg P g⁻¹ DM) than leaves, and species that sprout after fire ('re-sprouters') had significantly greater seed mass and P content than species that are killed by fire and regenerate from seed ('seeders'). Seeds contained only small amounts of polyphosphate (between 1.3 and 6 μg g⁻¹ DM), and this was not correlated with P concentration or fire response. Based on the evidence in the present study, we conclude that Banksia species are highly efficient in their use of P, explaining, in part, their success on P-impoverished soils, with little variation between species.